Analysis and Design of UMT Building - Qais Tanbour; Nabeel Bishtawy; Sabri Hasan; nedal aqel (My University, 2018)
A mathematical model for analysis and design of UMT Exhibition in Nablus is developed, using the finite element package(software) SAP2000, ETABS and SAFE. Shell, bracing, beam and column elements were used to simulate the building behavior. The modeling techniques were described. Checks for stiffness, strength adequacy and energy dissipation capacity of used members were performed in order to have a reliable load path. Equivalent lateral force and Modal Response Spectrum Analysis for building with viscus damping were developed. The effect of damping on the response of elastic, multiple-degree-of-freedom system was studied by linear analysis. A relatively simple nonlinear analysis method used to assess the behavior of structure under lateral load is performed using pushover analysis of a multi‐degree‐of‐freedom. Results for each method are illustrated. A comparison between the different methods is made. New structural systems for the building are suggested to be negotiated in future.